In Vivo Endoscopic Removal of Ancylostoma duodenale in a Patient with Abdominal Pain - Soo-Young Na; Heung Up Kim; Young Ree Kim; Seung Uk Jeong; Sun-Jin Boo; Hyun Joo Song; Eun Kwang Choi; Byung-Cheol Song (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
A 20-year-old Cambodian male living in Korea for 2 years as a foreign worker visited our gastroenterology outpatient clinic. He had a small farm in Cambodia. He complained of postprandial upper abdominal pain with nausea and vomiting for 2 years. Gastroduodenoscopy showed hyperemic mucosa near the major papilla in the duodenum and two small and slender reddish worms. These were removed with endoscopic biopsy forceps. Under microscopy, these were identified as Ancylostoma duodenale by the characteristic morphology of 2 pairs of cutting teeth in the buccal cavity and 3 lobes in the copulatory bursa. After removal of two worms, his symptom improved. Soil-transmitted helminths (STH) present a global health problem. In the Republic of Korea, STH, including hookworms, were highly prevalent until the 1970s. With mass fecal examination followed by selective mass chemotherapy with anthelmintics from 1969 to 1995, the prevalence of STH has rapidly decreased since the 1980s. Since 2004, no hookworms have been found in nationwide surveys on the prevalence of intestinal parasitic infection. Therefore, we report a case of in vivo endoscopic removal of A. duodenale in a patient with abdominal pain.